Academic neo-Marxism: scientific authenticity or paradigmatic utopia? - Mikhailouski, Vadzim S. (Journal of the Belarusian State University. Sociology, 2019)
It is proved that modern perception of neo-Marxism does not take into account presence of two opposing neo-Marxism tendencies: ideological humanistic and «scientistic» academic ones. The history of neo-Marxism itself shows that neo-Marxism methodology may differ: differ from its traditional perception as a biased ideological approach. It has been established on the basis of historical approach and content-analysis of Marxism and neo-Marxism text material that the ideologization of humanistic neo-Marxism, despite of opposition to party Marxism, despite of popularity among certain social strata (the New Left) and social and political activities of its theorists, was determined by a gnoseological reason – the initial bias towards cognizable reality. In such a situation, the method of humanistic neo-Marxism was a projection of the capitalist order on the ideal of non-alienated society, which suggested the research of capitalism not as a phenomenon that objectively exists, but as a phenomenon that should not exist. This led humanistic neo-Marxism to utopianism. Academic neo-Marxism accordance to primordial ideological neutrality of the whole neo-Marxism as well as academic neo-Marxism research parameters, which differ from humanistic neo-Marxism ones, were revealed. The author mentions anti-normativism, positivism and anti-psychologism among academic neo-Marxism research features. Anti-normativism means that a neo- Marxism feature has the sense that the goal-setting to change the world disappears from neo-Marxist research. Positivism is a neo-Marxism feature which has the sense that neo-Marxism strives for scientific objectivity. Anti-psychologism means that the goal of neo-Marxism cognition is to identify patterns of the social-economic order, and not to find new driving forces of history (agents of the revolution). Results received by the author have practical significance since revealed academic neo- Marxism is an experience and strategy for current neo-Marxism studies oriented on science.